2020
DOI: 10.1097/mao.0000000000002602
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation Outcomes and Prognostic Factors in Acoustic Neuroma Surgery: Predicting Cutoffs

Abstract: Objective: To investigate the outcomes of hearing preservation surgery (HPS) for acoustic neuroma and quantify tumor and patient characteristics predictive of hearing preservation after surgery. Study Design: Retrospective study. Setting: Tertiary referral center. Patients: A total of 100 consecutive patients diagnosed with acoustic neuroma from 2000 to 2012. Intervention: Hearing preservation surgery through microscopic retrosigmoid approach combined with a retrolabyrinthine meatotomy. Main Outcome Measure: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…When ABR abnormality increased postoperative hearing worsened (p = 0.001). In agreement with other authors [Brackmann et al, 2000;Zanoletti et al, 2020], type 5 ABR was associated with a poorer postoperative hearing. All the cases with postoperative anacusis had a preoperative abnormal ABR, mostly type 5.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When ABR abnormality increased postoperative hearing worsened (p = 0.001). In agreement with other authors [Brackmann et al, 2000;Zanoletti et al, 2020], type 5 ABR was associated with a poorer postoperative hearing. All the cases with postoperative anacusis had a preoperative abnormal ABR, mostly type 5.…”
Section: Discussionsupporting
confidence: 93%
“…There is a consensus in the literature that the most prognostic indicators for successful HP are tumor size <10 mm, good preoperative hearing and high speech discrimination score (SDS), shorter hearing loss period, and tumors from SVN [Bakkouri et al, 2009;Carlson et al, 2018;Huo et al, 2019]. In addition, there is some evidence that the auditory brainstem response (ABR) can provide prognostic information on prospects of HP [Brackmann et al, 2000;Hosoya et al, 2019;Zanoletti et al, 2020], since the ABR depends on neural synchrony and centripetal auditory-pathway integrity. The aim of the present work was to define an appropriate algorithm for the management of VS in a patient with NH can be diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies over the last ten years reported that cochlear implantation could safely be performed simultaneously with VS resection if the cochlear nerve was anatomically preserved and no overly aggressive manoeuvres were applied to remove the tumour. In addition to nerve preservation, audiological outcomes depended on tumour size in CPA and residual hearing function on the affected side [ 20 , 21 ]. Although a long-standing debate, an additional role may be played by a better contralateral hearing ear.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size and previous radiotherapy were identified as risk factors for hearing loss in our collective. In addition, impaired preoperative hearing has been found as a risk factor [ 5 , 57 ]. These variables should be considered for preoperative risk adjustment.…”
Section: Discussionmentioning
confidence: 99%